1993
DOI: 10.1111/j.1526-4610.1993.hed3308432.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Sumatriptan in the Acute Treatment of Migraine in Patients Using Dihydroergotamine as Prophylaxis

Abstract: The efficacy of sumatriptan, a 5-HT1 receptor agonist, in patients with migraine attacks occurring despite prophylactic treatment with oral dihydroergotamine, was assessed in a double-blind placebo-controlled study involving 76 patients. Thirty-seven patients were treated with a subcutaneous injection of 6 mg sumatriptan self-administered with an auto-injector and 39 with placebo given by the same route. Patients having inadequate relief were allowed to use a second injection of test medication 1 hour later an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 3 publications
(3 reference statements)
0
19
0
1
Order By: Relevance
“…Adverse events were more frequent in the sumatriptan group than in the other two groups. In the literature, rates of adverse events after treatment with sumatriptan s.c. vary from 27%[20] to 85% of patients [21]. In our trial, elevated blood pressure was the most commonly reported adverse event in all three groups, but it occurred most frequently in the sumatriptan group.…”
Section: Discussionmentioning
confidence: 68%
“…Adverse events were more frequent in the sumatriptan group than in the other two groups. In the literature, rates of adverse events after treatment with sumatriptan s.c. vary from 27%[20] to 85% of patients [21]. In our trial, elevated blood pressure was the most commonly reported adverse event in all three groups, but it occurred most frequently in the sumatriptan group.…”
Section: Discussionmentioning
confidence: 68%
“…Sumatriptan.-We identified 23 randomized trials of subcutaneous sumatriptan. 10,26,45,46,51,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] Fifteen placebo controlled studies revealed large and consistent statistically significant differences between sumatriptan and placebo in four class 1 studies, 64,66,68,70 seven class 2 studies, 54,56,58,60,61,63,67 and four class 3 studies. 55,57,62,65 In a class 1 study, 66 patients were randomized to sumatriptan 6 mg SC or prochlorperazine 10 mg 1 diphenhydramine 12.5 mg IV.…”
Section: Resultsmentioning
confidence: 99%
“…one was published twice [18], one was an interim analysis of a trial that was later published in full [19], one was a subgroup analysis of patients in two trials which had been published previously [20], one contained inconsistencies about the number of patients with adequate pain relief [21], one assessed pain relief but not at 2 h [22], and two did not provide data on the first administration in a cross-over design [23,24]. Thus a total of 22 trials, reported in 20 publications, were included in the analysis [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], including three trials in which the 2-h relief rates were obtained from the authors [30,34,39].…”
Section: Search For Studies and Inclusion Criteriamentioning
confidence: 99%